The Effect of Special Allocation Funds and Investment on Employment Absorption and Poverty Rate in the Sarbagita Region of Bali Province - Ni Komang Martha Cahyani Dharma Putri; Made Kembar Sri Budhi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Poverty remains a structural issue and a major challenge in economic development, including in Bali Province, particularly in the strategic Sarbagita region (Denpasar, Badung, Gianyar, and Tabanan). This region plays a significant role in supporting regional economic growth but still faces socioeconomic disparities, including a relatively high poverty rate. Several fundamental factors—such as limited investment in productive sectors, high unemployment rates, low quality of education, and uneven economic growth—are the primary causes of this issue. Targeted government expenditure policies and investment strategies directed toward areas with the potential to generate employment are expected to reduce poverty levels. This study aims to analyze the effect of Special Allocation Funds (DAK) and investment on employment absorption and poverty levels in the Sarbagita region of Bali Province from 2009 to 2023. The data used in this research are secondary data obtained from the Revenue Department, the Central Bureau of Statistics (BPS) in the Sarbagita Regional Area, and the Central Bureau of Statistics (BPS) of Bali Province. The analytical tool used in this study is path analysis with the assistance of SPSS software. The results indicate that DAK does not have a positive and significant effect on employment absorption in the Sarbagita region. Investment has a positive and significant effect on employment absorption. Employment absorption has a negative and significant effect on poverty levels in the region. DAK does not have a significant effect on poverty through employment absorption, whereas investment does have a significant effect on poverty through employment absorption in the Sarbagita region.